ASSESSMENT OF FREQUENCY OF ALLOIMMUNIZATION AND ERYTHROCYTE AUTOIMMUNIZATION IN TRANSFUSION DEPENDENT THALASSEMIA PATIENTS - S. Ansari; P. Voosogh S. Moshtaghian (Acta Medica Iranica, 2008)
Life-long red blood transfusion remains the main treatment for severe thalassemia. The development of hemolytic alloantibodies and erythrocyte autoantibodies complicated transfusion therapy in thalassemia patients. The frequency causes and prevention of this phenomenon among 80 transfused thalassemia patients were evaluated in Ali Asghar Children's Hospital during 1998-2004 in a cross-sectional study. In our study the mean age at the initiation of transfusion was 1.7 years (SD = 1.94) and mean interval of transfusion 33.73 day (SD = 20.74). Autoimmunization in 15 patients was positive and 8 patients had hemolytic reaction in transfusion. Our data show that alloimmunization to minor erythrocyte antigens and erythrocyte autoimmunization of significant clinical variables, are frequent findings in transfused thalassemia patients. However data suggest that prevalence of immunization in our patients is less than other Asian countries.